Ecofundamentalism : a critique of extreme environmentalism - Hannesson, Rögnvaldur (Lexington Books, 2014)
Ecofundamentalism: A Critique of Extreme Environmentalism is one of few books that focuses on ecofundamentalism, from its philosophical foundations to its policy prescriptions, instead of environmentalism as a whole. Ecofundamentalism places nature above man and is a possible threat to civilization. Rögnvaldur Hannesson critically examines central tenets of environmentalism such as sustainability, biodiversity, and the precautionary principle and he shows that issues like the "population bomb," global warming, and the depletion of the oceans are exaggerated or nonexistent threats.